Angiomatoid and desmoplastic Spitz nevus presenting as a keloidal nodule. Issue 4 (26th March 2018) - Yu, JiaDe; Jen, Melinda V.; Yan, Albert C.; Elenitsas, Rosalie; Rubin, Adam I.
Abstract: Angiomatoid and desmoplastic Spitz nevi are rare histologic variants of Spitz nevi that present most frequently on the extremities of children and young adults. Although Spitz nevi are clinically heterogeneous, one presenting as a keloidal nodule has not been previously published. We present a case of an angiomatoid and desmoplastic Spitz nevus clinically akin to a keloid on an African‐American teenager and describe its unique histopathologic features.